The changing structure of Africa’s economies - Diao, Xinshen; Harttgen, Kenneth; McMillan, Margaret S. (International Food Policy Research Institute, 2017)
In recent years, some counties in Africa south of the Sahara (SSA) have experienced growth in their economies and improvements in living standards. Although there is some debate, it is clear that the share of the population living below the poverty line fell significantly over the past decade and a half; there has been a general decline in infant mortality rates and increased access to education; in some of the fastest-growing economies, average growth rates have been positive for the first time in decades; and since the early 1990s, real consumption in SSA has grown between 3.4 and 3.7 percent per year. The reasons behind this so-called “African growth miracle” are not well understood, and to our knowledge, this paper is the first to connect these improvements in living standards to important occupational changes. Using data from the Groningen Growth and Development Center’s Africa Sector Database and the Demographic and Health Surveys, we show that much of SSA’s recent growth and poverty reduction has been associated with a substantive decline in the share of the labor force engaged in agriculture. This decline is most pronounced for rural females over the age of 25 who have a primary education. This has been accompanied by a systematic increase in the productivity of the labor force, as it has moved from low productivity agriculture to higher productivity services and manufacturing. We also show that although the employment share in manufacturing is not expanding rapidly, in most of the low-income SSA countries, the employment share in manufacturing has not peaked and is still expanding, albeit from very low levels. Although these patterns are encouraging, more work is needed to understand the implications of these shifts in employment shares for future growth and development in SSA.